The Dialectic of the Living Body (the actor) and the Dead Body (the Sinography Item) in the Construction of the Staged Image of the Play - Jasim Kadim Abd; Emad Hadi Abbas (الاكاديمي, 2019)
The current research deals with the dialectical relationship resulting from the conflict in the violent combination and construction of the living ( the actor)and the dead (the item) in the structure of the Sinography construction and the emergence of the theatrical play space , which can be summed up by the following question: what is the nature of the dialectical relationship between the living (the actor) and the dead( the item) in the Sinography creation, which limited the research in a central objective : to identify the controversy of the living (actor) and the dead (item) in the performance unit of the theatrical scene . The research, in its objective limits set forth in its methodological framework, analyzes this controversy in order to identify it and employ it procedurally. The research included the theoretical framework which identified the problem of the research, its importance, purpose, and the need for it, and also defined its terms procedurally. The research dealt with two sections: the first: the philosophy of the body, and the second: the nature of the dialectical relationship in the structure of the Sinography construction. It ended with the indicators of the theoretical framework. In the research procedures, a deliberate sample of the play "Dream in Baghdad" by Anas Abdul Samad was used. Finally, a set of findings and conclusions were reached at and the most important were the following: